Investigating the association between recorded smoking cessation interventions and smoking cessation in people living with cardiovascular disease using UK general practice data - Angela Difeng Wu; Nicola Lindson; Rafael Perera; Min Gao; Paul Aveyard; Rachna Begh; Jamie Hartmann-Boyce (BMC Primary Care)
Abstract Background Smoking significantly increases the risk of cardiovascular diseases (CVD), yet quitting smoking after diagnosis of CVD can mitigate further negative impacts. However, encouraging smoking cessation remains a challenge for General Practitioners (GPs) with concerns regarding mental health. Since 2004, the UK’s Quality and Outcomes Framework (QOF) incentivises GP smoking cessation support. Despite this, a significant proportion of individuals diagnosed with CVD continue to smoke after diagnosis. This study aims to investigate the frequencies and types of smoking cessation interventions offered to people with CVD (defined as coronary heart disease (CHD) and stroke), with and without mental illness, and assess their association with successful cessation. Methods This retrospective cohort study examined adults diagnosed with CHD or stroke using the QResearch general practice records database (1996–2019). We evaluated the frequency and types of smoking cessation interventions documented in patients’ records, including education, brief interventions, pharmacological support, referrals, and counselling. Logistic regression assessed the relationship between recorded interventions and smoking abstinence rates within the one-year post-index event, considering QOF incentives and mental illness presence. Results While smoking cessation education was common in general practice settings, prescriptions for nicotine replacement therapy or other evidence-based interventions were comparatively low. CHD and stroke populations showed a significant association between any intervention and smoking cessation within one year (CHD: OR 1.41, 95% CI 1.36–1.45; stroke: OR 1.49, 95% CI 1.43–1.55). Education consistently correlated with higher cessation likelihoods, while other interventions were linked to lower rates. Individuals with common and serious mental illness were less likely to quit, irrespective of intervention. QOF implementation led to increased documentation of advice but not intensive support or treatment, with pre-QOF interventions associated with significantly increased abstinence likelihoods (CHD: OR 5.09, 95% CI 4.84–5.35; stroke: OR 4.44, 95% CI 4.07–4.86). Conclusions Financial incentives for GP smoking cessation support outlined in QOF may not suffice to enhance methods that are more efficacious or improve cessation rates, especially among people with mental illness. Practical strategies that provide tangible support and treatment are needed for CVD patients, including those with mental illness, to facilitate successful cessation.